New Lactobacillus acidophilus isolates reduce the release of leptin by murine adipocytes leading to lower interferon-γ production - Bleau, C (Blackwell Science Inc, 2005)
Leptin produced by adipocytes increases Th1-dependent immunostimulation and autoimmune diseases. Lactobacilli are known to promote or suppress Th1 responses according to the isolates. We have investigated whether the sensitivity of Suriss Jim Lambert (SJL) mice to Th1-dependent immune diseases, when compared with C57BL/6 mice, may be modulated by selected lactobacilli able to decrease leptin release by adipocytes. White adipocytes were isolated from both C57BL/6 and SJL mice and incubated with bacterial extracts from new CBA4P and TPA3P isolates of Lactobacillus acidophilus and L. rhamnosus 9595 (LR), or with conditioned media (CM) from lactobacillus-treated macrophages. Immunomodulation induced by supernatants of treated adipocytes was determined by metabolic activity of syngenic splenic lymphocytes. Leptin produced by adipocytes, tumour necrosis factor (TNF)-α and interleukin (IL)-1β by macrophages, and IFN-γ and IL-4 by lymphocytes were quantified by enzyme-linked immunosorbent assay (ELISA) tests. Results revealed that supernatants from CBA4P- and LR-treated adipocytes decreased the metabolic activity of lymphocytes from SJL mice, whereas adipocytes incubated with CM from CBA4P-treated macrophages showed no stimulation of lymphocytes. Such effects correlated with leptin levels. Lower levels of leptin were produced by adipocytes from SJL mice in the presence of CBA4P and LR extracts. Lymphocytes from SJL mice produced low levels of IFN-γ when incubated with supernatants from CBA4P-treated cells. Such immunosuppressive effects were dependent on levels of TNF-α and IL-1β produced by lactobacillus-treated macrophages. Taken together, these results suggest that the CBA4P isolate reduces levels of leptin in SJL mice, leading to lower IFN-γ production. Therefore, the CBA4P isolate of L. acidophilus is a promising new probiotic strain for the control of Th1 inflammatory diseases.